2008
DOI: 10.1176/appi.ajp.2008.07121939
|View full text |Cite|
|
Sign up to set email alerts
|

Trauma, Resilience, and Recovery in a High-Risk African-American Population

Abstract: The identification of psychosocial factors associated with resistance to severe trauma can inform future studies of preventive and treatment interventions for high-risk populations. Further study is needed to determine which psychosocial factors are consistently associated with resilience and to what extent they can be modified through clinical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
160
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(170 citation statements)
references
References 45 publications
6
160
1
3
Order By: Relevance
“…Examples of this approach include the following: i) absence of psychopathology in high-risk samples (Alim et al, 2008;Parry et al, 2008); ii) in a chronic pain model, high scores on severity combined with low scores on interference and emotional burden (Karoly & Ruehlman, 2006); iii) from longitudinal observation, an increase in mental distress symptoms during exposure to adversity followed by a subsequent return back to pre-exposure levels (Netuveli et al, 2008).…”
Section: Measures Of Mental Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Examples of this approach include the following: i) absence of psychopathology in high-risk samples (Alim et al, 2008;Parry et al, 2008); ii) in a chronic pain model, high scores on severity combined with low scores on interference and emotional burden (Karoly & Ruehlman, 2006); iii) from longitudinal observation, an increase in mental distress symptoms during exposure to adversity followed by a subsequent return back to pre-exposure levels (Netuveli et al, 2008).…”
Section: Measures Of Mental Resiliencementioning
confidence: 99%
“…The use of absent (or low severity) psychopathology in a high-risk sample as an indicator of resilience may be evaluating a wide variety of different cognitive, somatic, behavioural and affective domains of mental disorder and thus may decrease the effect size of any specific resilience effect (Alim et al, 2008;Parry et al, 2008). The use of greater precision in terminology may help.…”
Section: Some Challenges For Future Resilience Researchmentioning
confidence: 99%
“…Not every individual who experiences stress develops features of depression or anxiety (Rutter, 1985;Southwick et al, 2005;Alim et al, 2008). Previous studies have identified subpopulations in rodent models that are resilient to the effects of stress (Kabbaj, 2004;Bergstrom et al, 2007;Krishnan et al, 2007;Sandi et al, 2008;Feder et al, 2009;Schmidt et al, 2010;Wood et al, 2010;Blugeot et al, 2011;Stiller et al, 2011;Taliaz et al, 2011;Castro et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On a personal level, for example, optimism has been confirmed as a protective factor in adults who experienced traumatic events such as earthquakes (Najarian et al 2011). Finding purpose in life may also be protective, as was found in atrisk adults who had been exposed to a range of severe traumas such as sexual or physical assault or assault with a weapon (Alim et al 2008). An internal locus of control and strong self-efficacy were found to be protective in adults who went through a number of risk experiences, such as poverty, hurricanes, or growing up with mentally ill parents (Werner and Smith 1992).…”
Section: Risks As Sources Of Mental Stress and Traumamentioning
confidence: 96%